Analisis Faktor Penerimaan Pengguna Aplikasi Fintech Menggunakan Unified Theory of Acceptance and Use of Technology 2 - Bernadine Zidane Maheswara; Nindita Aprilia; Wahyu Febryana Sari; Samso Supriyatna (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
The massive digital transformation in Indonesia's banking sector has created fierce competition among financial service providers, making it crucial to understand the psychological determinants of technology adoption. This study aims to analyze the factors that influence behavioral intention and use behavior in one of Indonesia's leading digital banking applications by adopting the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) framework. Using a quantitative approach, data were collected from 300 active users and analyzed using multiple linear regression to test the hypotheses between variables. The results show that all independent variables in the UTAUT2 model contribute positively and significantly to behavioral intention, with hedonic motivation and perceived value identified as the most dominant determinants, indicating that users now prioritize aspects of enjoyment and economic benefits over mere technical functionality. Furthermore, analysis of actual usage behavior shows that habit and behavioral intention are the main predictors, while facilitating conditions are not proven to have a significant direct impact